1992
DOI: 10.2166/wst.1992.0447
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Growth of Biomass on Surface-Modified Activated Carbon Fibers

Abstract: Activated carbon fiber (ACF) was used as a model of commercial activated carbons to examine the effect of surface chemistry on the attachment behavior of bacterial biomass. Surface acidity was found to enhance the biomass-ACF interaction. When ACFs were applied as biomass support media in a continuous stirred tank reactor, surface acidity of the carbon resulted in faster biomass growth in the start-up phase. The start-up phase was simulated by a simple biomass attachment kinetics model. Experimental and calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This decrease was higher in AAC as compared to BAC because after HNO 3 modification, there was a chance that the surface of the smaller microspores was reacted and blocked by complex functional groups containing mainly carboxylic acids with small amount of phenol, anhydrides and lactones (Kutics and Suzuki 1990;Figueiredo et al 1999), generated during nitric acid treatment (Donnet and Bansal 1990). In BET measurements of dry ACs sample, these pores were not assessed, despite the small molecular size of nitrogen gas.…”
Section: Characterization Of the Activated Carbonsmentioning
confidence: 99%
“…This decrease was higher in AAC as compared to BAC because after HNO 3 modification, there was a chance that the surface of the smaller microspores was reacted and blocked by complex functional groups containing mainly carboxylic acids with small amount of phenol, anhydrides and lactones (Kutics and Suzuki 1990;Figueiredo et al 1999), generated during nitric acid treatment (Donnet and Bansal 1990). In BET measurements of dry ACs sample, these pores were not assessed, despite the small molecular size of nitrogen gas.…”
Section: Characterization Of the Activated Carbonsmentioning
confidence: 99%
“…8) indicates that the bacteria count in the first period (November 15-17, 1999) for only S0.8 carbon was lower in comparison with the later days (November [19][20][21][22][23][24][25]1999). This was due to the short bed operation time and longer time needed to the maturation process for this sample.…”
Section: Resultsmentioning
confidence: 99%
“…Activated carbon is characterized by the presence of manmade and inherent crevices, ridges, surface groups, and other surface irregularities, all of which provide a perfect environment for colonization in macropores; consequently, colonization is denser on such a substrate than on conventional filters [19][20][21][22]. In this connection, bacteriological analysis of water has shown that bacteria settle on the filter material, reproduce on it, and take part in the maturing process.…”
Section: Introductionmentioning
confidence: 99%